Can We Talk Mediterranean?
XXI, 153 p. 5 illus., 3 illus. in color.
Keywords: This book provides a systematic framework for the emerging field of Mediterranean studies, collecting essays from scholars of history, literature, religion, and art history that seek a more fluid understanding of “Mediterranean.” It emphasizes the interdependence of Mediterranean regions and the rich interaction (both peaceful and bellicose, at sea and on land) between them. It avoids applying the national, cultural and ethnic categories that developed with the post-Enlightenment domination of northwestern Europe over the academy, working instead towards a dynamic and thoroughly interdisciplinary picture of the Mediterranean. Including an extensive bibliography and a conversation between leading scholars in the field, Can We Talk Mediterranean? lays the groundwork for a new critical and conceptual approach to the region.